2012
DOI: 10.1002/jbm.a.34006
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion, activation, and aggregation of blood platelets and biofilm formation on the surfaces of titanium alloys Ti6Al4V and Ti6Al7Nb

Abstract: Titanium alloys are still on the top list of fundamental materials intended for dental, orthopedics, neurological, and cardiovascular implantations. Recently, a special attention has been paid to vanadium-free titanium alloy, Ti6Al7Nb, that seems to represent higher biocompatibility than traditional Ti6Al4V alloy. Surprisingly, these data are not thoroughly elaborated in the literature; particularly there is a lack of comparative experiments conducted simultaneously and at the same conditions. Our study fills … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…One example of such a search is an attempt to replace commonly used in medicine Ti6Al4V alloy by Ti6Al7Nb alloy. The latter has better corrosion resistance and does not release toxic vanadium, and is also assigned to other positive traits …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One example of such a search is an attempt to replace commonly used in medicine Ti6Al4V alloy by Ti6Al7Nb alloy. The latter has better corrosion resistance and does not release toxic vanadium, and is also assigned to other positive traits …”
Section: Discussionmentioning
confidence: 99%
“…The latter has better corrosion resistance [4][5][6][7] and does not release toxic vanadium, and is also assigned to other positive traits. [12][13][14] The literature delivers different and often contradictory information on cells' proliferation on the surfaces of these alloys. The article 15 shows that the oxidized and nonoxidized surfaces of both alloys in different manner affected proliferation of osteoblast-line Saos-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The manufacturers of the Heartmate‐II and other continuous flow VADs currently use a polished titanium alloy (Ti6Al4V) as the blood contacting surface due to its desirable mechanical properties, resistance to corrosion, and tolerable blood compatibility . However, in vitro studies have shown that this alloy exhibited elevated acute thrombogenicity compared to other coated surfaces (e.g., polyethylene glycol and diamond‐like coatings) or related alloys (Ti6Al7Nb) . This study was therefore conducted to perform a systematic side‐by‐side comparison of six candidate biomaterials currently being considered for application in continuous‐flow blood pumps.…”
Section: Introductionmentioning
confidence: 99%
“…11 However, in vitro studies have shown that this alloy exhibited elevated acute thrombogenicity compared to other coated surfaces (e.g., polyethylene glycol and diamond-like coatings) or related alloys (Ti6Al7Nb). 2,5,12,13 This study was therefore conducted to perform a systematic side-by-side comparison of six candidate biomaterials currently being considered for application in continuous-flow blood pumps. However, since these materials are opaque, traditional methods for real time visualization of platelet deposition, such as fluorescent microscopy utilizing whole blood, are not readily applicable.…”
Section: Introductionmentioning
confidence: 99%